ANALISIS KEMAMPUAN KOGNITIF SISWA PADA MATERI PEMANASAN GLOBAL DI SMA PERSIAPAN STABAT - Haryati; Anisa Noverita; Unita Sukma Zuliani Nasution; Eka Darliana; Tya Astuti (Jurnal Sintaksis, 2025)
This study focuses on "Analysis of Students' Cognitive Abilities on Global Warming Materials in Stabat Preparatory High School". The purpose of the research is to find out the understanding of Biology learning in the cognitive realm in the XIC Science class of Stabat Preparatory High School. Descriptive research method with the form of survey study research, with a population of grade XI students. Data collection tools for interviews, questionnaires, test questions and documents. The results of the study show that from the results of the test questions faced to students, it can be seen that there are 16 students who have cognitive abilities that are included in the good category and there are 5 students who are included in the sufficient category. Based on these results from the 21 samples taken, it can be said that the cognitive abilities of students in Biology learning are quite good. And if the percentage of 84.33% of students who understand well and 17.76% of students understand adequately the test questions that are being done.